Pengaruh Daya Tarik Produk Pesaing dan Kepuasan Konsumen terhadap Perpindahan Merek - Isti Pujihastuti; Viranti Rahayu (Fakultas Ekonomi Universitas Islam 45, 2023)
This study aims to determine the effect of competitor product attractiveness and customer satisfaction on the decision to switch from other brands of instant noodles to Indomie in Bekasi City. Descriptive study using a quantitative approach is the methodology used. Partially, the attractiveness of competing products has a positive and significant effect on brand switching, customer satisfaction has a positive and significant effect on brand switching so that it is not proven, perhaps as a result of the vigorous marketing campaign, wide variety of flavors, and higher quality of Indomie instant noodles. The findings of the coefficient of determination show that the R square value of 65% of the independent variables can be explained by the dependent variable, while the remaining 35% can be explained by other variables not included in this study.